2018
DOI: 10.1038/s41598-018-34453-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Fat Diet Programs Offspring Liver Steatosis in a Sexually Dimorphic Manner in Association with Changes in Gut Microbial Ecology in Mice

Abstract: The contributions of maternal diet and obesity in shaping offspring microbiome remain unclear. Here we employed a mouse model of maternal diet-induced obesity via high-fat diet feeding (HFD, 45% fat calories) for 12 wk prior to conception on offspring gut microbial ecology. Male and female offspring were provided access to control or HFD from weaning until 17 wk of age. Maternal HFD-associated programming was sexually dimorphic, with male offspring from HFD dams showing hyper-responsive weight gain to postnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 80 publications
6
80
0
1
Order By: Relevance
“…Early-life adversity has been linked to offspring metabolic dysfunction (Elahi et al 2009;Howie et al 2009;Morris & Chen, 2009). More recently, because intestinal microbial interactions with the host have been shown to modulate metabolism , several groups have shown that early adversity is associated with changes offspring gut bacterial composition Robertson et al 2018;Soderborg et al 2018;Wankhade et al 2018). Because intestinal bacteria interact with and modulate gut epithelial structure, mucosal thickness, barrier integrity and immune composition, we propose that changes in offspring metabolic × gut interactions may be downstream of altered fetal intestinal structure and development.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Early-life adversity has been linked to offspring metabolic dysfunction (Elahi et al 2009;Howie et al 2009;Morris & Chen, 2009). More recently, because intestinal microbial interactions with the host have been shown to modulate metabolism , several groups have shown that early adversity is associated with changes offspring gut bacterial composition Robertson et al 2018;Soderborg et al 2018;Wankhade et al 2018). Because intestinal bacteria interact with and modulate gut epithelial structure, mucosal thickness, barrier integrity and immune composition, we propose that changes in offspring metabolic × gut interactions may be downstream of altered fetal intestinal structure and development.…”
Section: Introductionmentioning
confidence: 84%
“…; Wankhade et al . ). Because intestinal bacteria interact with and modulate gut epithelial structure, mucosal thickness, barrier integrity and immune composition, we propose that changes in offspring metabolic × gut interactions may be downstream of altered fetal intestinal structure and development.…”
Section: Introductionmentioning
confidence: 97%
“…These results suggest that the male offspring of GD rats are more susceptible to disturbances in body weight, when they are exposed to a high maternal blood glucose level during the middle stage of pregnancy. In this regard, sexual differences in the offspring body weight have been reported in relation to maternal obesity and a maternal high-fat diet model [38,39], where it was shown that the body weight of female offspring did not change.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota link between the mother and offspring is continued at and after birth by microbes present during delivery as well as postnatal breast milk [19]. Perinatal HF diet was reported to alter gut microbiota in adult offspring [20]. These findings suggest that gut microbiota and its metabolites not only impact hypertension development but also serve as a link between mothers consuming a diet high in saturated fat and programmed hypertension in their adult offspring.…”
Section: Introductionmentioning
confidence: 97%